Participation of the vegetative system on paroxismality and formation of posttraummatic epilepsy - O. M. Stoyanov; O. O. Kolesnik; S. S. Mashchenko; S. A. Antonenko; A. O. Kaptalan (Kazimierz Wielki University, 2016)
The article deals with the involvement of the autonomic nervous system in the formation of symptomatic epilepsy as the consequences of a craniocerebral trauma. The problems of comprehensiveness of such epileptogenezis involving in pathological process of suprasegmental divisions of the autonomic nervous system, the limbic system and other deep structures of the central nervous system, the brain stem and peripheral autonomic entities, who are actively involved in maintaining the paroxysm of the process in the body vegetative response at different periods сonvulsive paroxysm. Knowing the features of participation and the degree of involvement of certain structures of the vegetative system, one can plan a therapeutic effect on their activity for adequate pathogenetic treatment of such consequences of craniocerebral trauma.